The Influence of Additional Treatments on the Survival of Patients Undergoing Transarterial Radioembolization (TARE) - Natale Quartuccio; Salvatore Ialuna; Daniele Scalisi; Fabio D’Amato; Maria Rosa Barcellona; Maria Grazia Bavetta; Giorgio Fusco; Enrico Bronte; Emma Musso; Fabrizio Bronte; Viviana Picciotto; Antonio Carroccio; et al. (Current Oncology, 2024)
The aim of this study was to present our preliminary experience with transarterial radioembolization (TARE) using Yttrium-90 (90Y), compare the cancer-specific survival (CSS) of patients with hepatocellular carcinoma (HCC) and colorectal cancer (CRC) liver metastases undergoing TARE, and investigate the influence of additional treatments on CSS. Our database was interrogated to retrieve patients who had undergone TARE using Yttrium-90 (90Y) glass or resin microspheres. Kaplan–Meier curves and the log-rank test were employed to conduct survival analysis for the different groups (p < 0.05). Thirty-nine patients were retrieved (sex: 27 M, 12 F; mean age: 63.59 ± 15.66 years): twenty-three with hepatocellular carcinoma (HCC) and sixteen with CRC liver metastasis. Globally, the patients with HCC demonstrated a significantly longer CSS than those with CRC liver metastasis (22.64 ± 2.7 vs. 7.21 ± 1.65 months; p = 0.014). Among the patients with CRC liver metastasis, those receiving TARE and additional concomitant treatments (n = 10) demonstrated a longer CSS than the CRC patients receiving only TARE (9.97 ± 2.21 vs. 2.59 ± 0.24 months; p = 0.06). In the HCC group, there was a trend of a longer CSS in patients (n = 8) receiving TARE and additional treatments (27.89 ± 3.1 vs. 17.69 ± 3.14 months; p = 0.15). Patients with HCC seem to achieve a longer survival after TARE compared to patients with CRC liver metastases. In patients with CRC liver metastases, the combination of TARE and additional concomitant treatments may improve survival.